UV Photoluminescence of Eu3+doped Na3SO4F Red Halosulphate Phosphor for White Light Emitting Diodes - S. T. Taide, (International Journal of Scientific Research in Science and Technology, 2024)
The high luminescent Na3SO4F: Eu3+ halosulphate phosphor with improved the color purity and high intensity of red phosphor for solid state lighting devices was reported. The halosulphate phosphor was developed by re-crystallization technique. Crystal structure and phase formation of the product was identified by powder XRD technique and particle morphology was studied by FE-SEM. The photoluminescence (PL) spectra were investigated under 393nm (UV) excitation. The prepared halosulphate Na3SO4F: Eu3+ phosphor showed a strong red emission around 617 nm. This is due to Eu3+ substituted for Na3+ occupied the non centro-symmetric position. The Eu3+ doped ion will increase the electric dipole 5F0®7D2 transition of Eu3+ in the crystal structure of Na3SO4F: Eu3+. It can be concluded that re-crystallization technique can successfully employed to promising red phosphor for solid state lighting devices.
Keywords: Photoluminescence; Halosulphate Phosphors; Re-Crystallization